(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Human immunodeficiency virus (HIV) infection remains a health challenge in Nigeria, and women of reproductive age are disproportionately infected. P53 protein, D-dimer, serum ferritin, CD4 cell count, haemoglobin concentration and haematocrit levels were measured among non-pregnant women of reproductive age living with HIV infection in order to assess the impact of HIV infection on maternal health. A hundred and sixty-two subjects categorised into three groups of 54 persons each involving; newly diagnosed, subjects on highly active antiretroviral therapy (HAART) and apparently healthy control subjects were recruited. Blood samples were analyzed for haemoglobin concentration, haematocrit, CD4 cell count, serum ferritin, D-dimer and p53 protein levels by standard methods. The CD4 cell count, serum p53 protein, and Hb Conc. were significantly lower, while serum ferritin was higher in the newly diagnosed group (p=0.001), followed by the group on HAART (p=0.001) compared to the controls. D-dimer level was significantly lower in the control group (2899.11±670.73pg/ml) than both newly diagnosed (4842.44±489.40pg/ml) and HAART (4660.31±519.83pg/ml) groups, while significant decrease in haematocrit was observed between the newly diagnosed group (0.336±0.07l/l) as against both treated (0.378±0.04l/l) and control (0.362±0.02l/l) groups. D-dimer correlated negatively with serum p53 protein level among the newly diagnosed subjects and with Hb Conc. among subjects undergoing treatment. The study concludes that women of reproductive age living with HIV infection showed higher D-dimer and lower tumour suppression protein levels as well as anaemia and reduced immune response. The newly diagnosed subjects were more affected